A review of the green syntheses and anti-microbial applications of gold nanoparticles. Issue 4 (2nd October 2017) - Nadeem, Muhammad; Abbasi, Bilal Haider; Younas, Muhammad; Ahmad, Waqar; Khan, Taimoor
ABSTRACT: Nanotechnology has emerged as a promising multidisciplinary field. It has shown several applications including diagnostics, imaging and structural design. Nanoparticles can be synthesized via chemical and physical approaches, carrying many threats to the ecosystem. To overcome these threats, sustainable routes for the synthesis of nanoparticles were implemented. Green synthesis is the most fascinating and attractive alternative to chemical synthesis as it offers more advantages. Nontoxic and eco-friendly secondary metabolites from plants are used as reducing and capping agents. This process is comparatively simple and cost-effective. A gold salt is simply reduced by biomolecules (phenols, alkaloids, proteins, etc.) present in the extracts of these plants. In this review, we have emphasized the synthesis and antimicrobial potential of gold nanoparticles using various plant extracts and their proposed mechanisms. Abbreviation : Au: aurum; gold; DLS: dynamic light scattering; EDAX: energydispersive X-ray analysis; EDS: energy-dispersive spectroscopy; FTIR: Fourier transform infrared spectroscopy; HRTEM: highresolution transmission electron microscopy; NPs: nanoparticles; UV–VIS: ultra violet-visible spectroscopy; SEM: scanning electron microscopy; XRD: X-ray Diffraction GRAPHICAL ABSTRACT: